Design Models of Equipment Vapor Compression Refrigeration Cycle To Support Practicum Heat Engine And Fluid Engineering - Mikraj, Hadimi; Rahmadi, Joni; Marlina, Dina; Rusadi, Rusadi; Karyadi, Edi (Vokasi: Jurnal Publikasi Ilmiah, 2024)
The learning method acts as an educational facility that functions to convey learning material to achieve learning goals. It takes creativity from lecturers and those responsible for the teaching and learning process, especially practicum. The results of the study entitled Design Models of Equipment Vapor Compression Refrigeration Cycle To Support Practicum Heat Engine And Fluid Engineering Subject produce a model of a practicum tool that can be used to carry out some practicum contents for refrigeration engines. This model of Vapor Compression Refrigeration Cycle can do several practicums in a refrigeration machine, namely looking for COP from a refrigeration machine, installing a refrigeration machine, incubating a refrigeration machine, pumping down a refrigeration machine and filling in a refrigerating machine. Keywords: Model tools, Vapor Compression, Practicum